1974
DOI: 10.3758/bf03199292
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing of auditory and phonetic information in speech discrimination

Abstract: Recent experiments using a variety of techniques have suggested that speech perception involves separate auditory and phonetic levels of processing. Two models of auditory and phonetic processing appear to be consistent with existing data: (a) a strict serial model in which auditory information would be processed at one level, followed by the processing of phonetic information at a subsequent level; and (b) a parallel model in which auditory and phonetic processing could proceed simultaneously. The present exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
5

Year Published

1975
1975
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 37 publications
9
75
5
Order By: Relevance
“…This term has been applied to cases in which the amounts of interference on two orthogonal dimensions are unequalcases in which one of two orthogonally varied dimensions produces interference whereas the other does not (Garner, 1974, referring to Day & Wood, 1972, and Wood, 1974, and cases in which one of the dimensions produces greater interference than the other (Pomerantz & Sager, 1975). Apparent "asymmetric integrality" is not readily explicable by Garner's theory of two types of internal representations.…”
Section: Resultsmentioning
confidence: 99%
“…This term has been applied to cases in which the amounts of interference on two orthogonal dimensions are unequalcases in which one of two orthogonally varied dimensions produces interference whereas the other does not (Garner, 1974, referring to Day & Wood, 1972, and Wood, 1974, and cases in which one of the dimensions produces greater interference than the other (Pomerantz & Sager, 1975). Apparent "asymmetric integrality" is not readily explicable by Garner's theory of two types of internal representations.…”
Section: Resultsmentioning
confidence: 99%
“…Given the numerous recent studies suggesting that the processing of speech and nonspeech acoustic signals is subserved by a common set of auditory analyzers (e.g., Cutting & Rosner, 1974;Eimas & Miller, in press;Kuhl & Miller, 1975), it seems much more likely that a mutual asymmetric dependency is just one of many forms of dependency that exists within the auditory system. (Blechner et al, 1976;Pastore et al, 1976, Experiment 5;Wood, 1974) have shown an asymmetric interference effect and a redundancy gain. One explanation of this combination of effects is "that subjects have some degree of freedom about the kinds of processing that they use in different task conditions" (Blechner et aI., 1976, p. 259).…”
Section: Discussionmentioning
confidence: 96%
“…Inasmuch as our instructions for the correlated tasks did not emphasize the correlated nature of the stimuli, as they did in the Wood (1974) and Blechner et al (1976) studies, we replicated Experiment I with instructions that informed listeners about the nature of the stimuli and that further informed them "to try and use the correlation between the two dimensions to help you respond as quickly as you can." Despite this change, a true redundancy gain (or for that matter any form of correlated effect) failed to appear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Day and Wood (1972a) and Wood (1974Wood ( ,_ 1975 found that irrelevant variation in a non linguistic dimension of a CV syllable (fundamental frequency) produced su bstantial interference with identitication of a linguistic dimension (the initial stop consonant). In contrast.…”
Section: Linguistic and Nonlinguistic Dimensionsmentioning
confidence: 99%